The Role of Prosecutor's Investigators in Handling Corruption Crimes of Family Planning Operational Assistance Fund Embezzlement in Tanggamus Regency - Budi Setiawan SP; Rinaldy Amrullah; Muhtadi Muhtadi (Journal of Law and Economics, 2025)
Corruption remains a heavy burden for Indonesia in its quality as an extraordinary crime since it has very broad implications for aspects of governance, development, and public trust in state institutions. This study aims to analyze the role of prosecutor's investigators in handling corruption cases related to the illegal deduction of Family Planning Operational Assistance (BOKB) funds in Tanggamus Regency. The research methodology used normative and empirical juridical approaches with primary data collected through interviews with law enforcement officials and secondary data sourced from statutory provisions, case files, and scientific literature. The Tanggamus District Prosecutor's Office carried out the main tasks at the stages of investigation, indictment, and prosecution. In case Number PDS/02/TGMS/07/2022, investigators revealed a systematic scheme where 17.5% was deducted from every fund disbursement causing state financial losses amounting to approximately IDR 1.55 billion. Several barriers were faced during the investigation; witness testimonies were inconsistent, facilities and infrastructure were inadequate, and forensic audits to calculate state losses faced delays. Increasing inter-institutional coordination between prosecutors and related agencies as well as improving infrastructural capacity is necessary to increase both legitimacy and effectiveness in corruption eradication.